The role of number-of-excitations (NEX) for the usability of free-breathing acquired diffusion-derived ‘vessel density’ (DDVD) and slow diffusion coefficient (SDC) maps in separating liver cysts, hemangiomas, and solid masses with a focus on small lesions - Sun, Ming-Hua; Li, Cai-Ying; Xu, Xin-Yue; Xu, Chuan-Jun; Rong, Peng-Fei; Wáng, Yì Xiáng J. (Journal of Gastrointestinal Oncology; Vol 17, No 3 (June 29, 2026): Journal of Gastrointestinal Oncology, 2026)
Background: Diffusion weighted imaging has been commonly used to non-invasively characterize liver space occupying lesions. This study investigates the role of number-of-excitations (NEX) for free-breathing acquired diffusion-derived ‘vessel density’ (DDVD) and slow diffusion coefficient (SDC) maps in separating liver solid mass-forming lesions (MFL), cysts, and hemangiomas (HG) with a focus on small lesions.Methods: Liver diffusion weighted imaging data were acquired at two centers using 3.0 T scanners, applying a free-breathing single-shot spin-echo type echo-planar sequence. For Center 1 (The Fifth Affiliated Hospital of Anhui Medical University) data, DDVD was calculated with b=0 and b=10 s/mm2 images (both NEX =2) and SDC was calculated with b=400 and b=600 s/mm2 images (both NEX =4). For Center 2 (The Second Hospital of Nanjing) data, DDVD was calculated with b=0 and b=10 s/mm2 images and SDC was calculated with b=600 and b=800 s/mm2 images (all NEX =6). In total there were 148 MFLs (91 hepatocellular carcinomas, 11 intrahepatic cholangiocarcinomas, 33 metastases, 13 focal nodular hyperplasias), 22 cysts, and 45 HGs.Results: The MFLs had a median size of 2.9 cm (range: 0.6–25 cm). Counting lesion-by-lesion, 2% of MFLs’ SDC maps were not usable, while 16.2% of MFLs’ DDVD maps were not usable. MFLs with unusable SDC map or DDVD map had mostly a size